Comparing two‐step and one‐step chromatic adaptation transforms using the CAT16 model. Issue 5 (15th August 2018) - Li, Changjun; Xu, Yang; Wang, Zhifeng; Luo, Ming Ronnier; Cui, Guihua; Melgosa, Manuel; Brill, Michael H.; Pointer, Michael
Abstract: Color‐appearance models, CIECAM02 and CAM16, usually include two one‐step chromatic adaptation transforms: a forward (one‐step) transform to convert data from a first illuminant to CIE illuminant E, plus a reverse (one‐step) transform to convert the results from CIE illuminant E to a second illuminant. In practice, however, one‐step chromatic adaptation models, that avoid the use of the intermediate CIE illuminant E, are also employed. Tests using the one‐step CAT16 model indicate failures of both the symmetry and transitivity properties, except in the case where the degree of adaptation D is equal to unity. The magnitude of these failures depends on the specific illuminants selected, and increases as the degree of adaptation decreases. From four possible two‐step CAT16 models, we have identified two that obey the symmetry and transitivity properties, one with slightly better predictions of the experimental corresponding‐color datasets available in the literature, and more consistent with the one‐step CAT16 model. The findings of this article confirm that, for incomplete adaptation, the use of the one‐step CAT is incorrect, and we propose that the use of a two‐step CAT16 model be mandatory for future applications.